The Glenolabral Articular Disruption Lesion Is a Biomechanical Risk Factor for Recurrent Shoulder Instability - Jens Wermers, M.Sc; Benedikt Schliemann, M.D; Michael J. Raschke, M.D; Felix Dyrna, M.D; Lukas F. Heilmann, M.D; Philipp A. Michel, M.D; J. Christoph Katthagen, M.D (Elsevier, 2021)
Purpose: To investigate the biomechanical effect of a glenolabral articular disruption (GLAD) lesion on glenohumeral laxity. Methods: Human cadaveric glenoids (n = 10) were excised of soft tissue, including the labrum to focus on the biomechanical effects of osteochondral surfaces. Glenohumeral dislocations were performed in a robotic test setup, while displacement forces and three-dimensional morphometric properties were measured. The stability ratio (SR), a biomechanical characteristic for glenohumeral stability, was used as an outcome parameter, as well as the path of least resistance, determined by a hybrid robot displacement. The impacts of chondral and bony defects were analyzed related to the intact glenoid. Statistical comparison of the defect states on SR and the path of least resistance was performed using repeated-measures ANOVA and Tukey's post hoc test for multiple comparisons (P < .05). The relationship between concavity depth and SR was approximated in a nonlinear regression. Results: The initial SR of the intact glenoid (28.3 ± 7.8%) decreased significantly by 4.7 ± 3% in case of a chondral defect (P = .002). An additional loss of 3.2 ± 2.3% was provoked by a 20% bony defect (P = .004). The path of least resistance was deflected significantly more inferiorly by a GLAD lesion (2.9 ± 1.8°, P = .002) and even more by a bony defect (2.5 ± 2.9°, P = .002). The nonlinear regression with concavity depth as predictor for the SR resulted in a high correlation coefficient (r = .81). Conclusions: Chondral integrity is an important contributor to the SR. Chondral defects as present in GLAD lesions may cause increased laxity, influence the humeral track on the glenoid during dislocation, and represent a biomechanical risk factor for a recurrent instability. Clinical Relevance: Cartilage deficiency corresponding to GLAD lesions may be a risk factor for impaired surgical outcomes.